Is the Internet Changing our Conception of Democracy? an analysis of Internet use During protests and Its effect on the perception of Democracy - Sajuria, Javier (Política. Revista de Ciencia Política, 2013)
<!–[if gte mso 9]> <![endif]–> <!–[if gte mso 9]> Normal 0 21 false false false EN-US JA X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> The last several years have seen the rise of social movements around the globe, such as the student protests in the UK and Chile, the Arab Spring, the Indignados, and the Occupy movement. They represent different political aspirations, but all of them relied heavily on the Internet to communicate and organise. This research analyses two specific contentious processes - the UK student protests and the Chilean environmentalist protests in 2010 - to assess the effect that the Internet may have had on the protesters’ perception of democracy. Through data gathered from online surveys, interviews, and the Oxford Internet Survey 2009, this article observes the effect of the Internet in two dimensions: support for democracy, and the protesters’ conception of democracy. Preliminary results show that Internet use is related to a more horizontal conception of democracy, and that more analyses are required to test whether that association is caused by the Internet or a utopian discourse about it.